Effect of repeated through-and-through joint lavage on serum amyloid A in synovial fluid from healthy horses. (April 2016) - Sanchez-Teran, A.F.; Bracamonte, J.L.; Hendrick, S.; Riddell, L.; Musil, K.; Hoff, B.; Rubio-Martínez, L.M.
Highlights: Three through-and-through lavage of the tarsocrural joint were performed on six healthy horses. Total protein and nucleated cell count in synovial fluid increased 24 h after the first lavage. Percentages of neutrophils in synovial fluid were affected by blood contamination during sampling. Serum amyloid A in synovial fluid was not affected by repeated joint lavage. Serum amyloid A in synovial fluid might serve for monitoring sepsis during treatment. Abstract: The objective of this study was to evaluate the effect of through-and-through joint lavage on systemic and synovial serum amyloid A (SAA), total protein, nucleated cell count and percentage of neutrophils in the synovial fluid of six healthy horses. A prospective experimental study was performed where one healthy tarsocrural joint of each horse was randomly assigned to receive repeated through-and-through joint lavage at 0, 48 and 96 h. Synovial fluid and blood samples were collected at 0 (baseline), 24, 48, 72, 96 and 120 h. Systemic and synovial SAA, total protein, nucleated cell count and percentage of neutrophils were measured and compared to baseline. Concentrations of systemic and synovial SAA percentage of neutrophils were not increased from baseline in contrast to total protein and nucleated cell counts (except for nucleated cell count at 96 h). In conclusion, repeated through-and-through joint lavage did not affect synovial SAA concentrations in horses; however, synovial total protein and nucleated cell count values increased. Some of the total protein and nucleated cell count values observed in this study were within the range reported for septic arthritis 24 h after joint lavage. Hence, synovial SAA may be a valuable marker to evaluate the clinical progression of septic joints after through-and-through joint lavage. Clinical studies evaluating synovial fluid SAA concentrations while treating synovial sepsis with through-and-through joint lavage are warranted.